HUBUNGAN KEBIASAAN MENGGUNAKAN HEADSET BLUETOOTH DENGAN PEMAHAMAN TERHADAP RADIASI - Bisra, Marido; Adha, Afifah Cahayani; Indra, Hamdi (Journal of Hospital Administration and Management (JHAM), 2023)
A Bluetooth headset is a combined device of headphones and microphone that functions by connecting a Bluetooth device to a smartphone or other communication device. Bluetooth headsets contain a type of non-ionizing radiation that has the potential to cause health problems. However, it seems that many people and students still do not know about the effects of radiation exposure from Bluetooth devices and the use of headsets that can be harmful to health. The research method used is quantitative research with a survey approach and tested with the Spearman Rank test. This analysis was carried out with a population of students at SMAN 10 Pekanbaru and a sample of 45 people. The Spearman Rank test results obtained were a sig (2-tailed) value of 0.286 with a confidence interval of α 0.05 for the 2-tailed test. The conclusion is drawn that H0 is accepted and H1 is rejected. The correlation coefficient value is -0.162 indicating the level of strength of the relationship between variables, there is almost no correlation and the correlation coefficient is negative, which means that the relationship between the variables is not unidirectional. Based on the results obtained, it can be ascertained that there is no relationship between students' understanding of radiation and the use of Bluetooth headsets.